SISTEM PENDIDIKAN MA’AD ‘ALY - Kurniawan, M. Agus; Mukhlishin, Ahmad (Journal of Islamic Education and Learning, 2022)
Ma'had Aly was formed in order to prepare cadres of ulama' who have scientific, amaliah and khuluqiyah integrity that are qualified and have strategic values ??that are oriented towards justice, equality, openness, honesty, trust, and populist. Ma'had Aly based on Ahlus Sunnah Wal Jama'ah with an Islamic basis means that Ma'had Aly is held, organized, and developed from the point of depture from Islamic teachings, the management process is Islamic and towards what is idealized by Islamic education. In the dynamics of Islamic boarding school education, it is explained that the development of Islamic boarding schools has experienced a shift or change in several aspects along with the progress of the times and the development of science and technology.